Disruption of Undergraduate Clinical Training in Postconflict Syria: Insights from Clinical Practice and Implications for Future Health Workforce Readiness - Rawan Al-Deeb; Taim Al Kheder; Mohammad Al-Akchar (Avicenna Journal of Medicine, 2026)
Abstract Clinical training is a fundamental component of medical education and plays a critical role in preparing future physicians for clinical practice. In Syria, the prolonged effects of conflict continue to shape health care institutions and training environments despite the decline of large-scale hostilities. Drawing on firsthand observations from clinical-stage medical students at Syrian public universities, we highlight recent changes in undergraduate clinical training, together with recent policy changes that discontinued practical assessments for fourth- and fifth-year students and concentrated formal clinical assessment within the final year of study. While these changes may reflect resource and institutional constraints, they may also limit opportunities for the gradual development and reinforcement of clinical competencies. Given existing evidence of gaps in practical preparedness among Syrian medical students, preserving meaningful clinical exposure and competency-based assessment throughout the clinical years should remain a priority for medical schools and policymakers as Syria rebuilds its future health workforce.